Biomechanical Comparison of Different Volar Fracture Fixation Plates for Distal Radius Fractures - Sobky, Kareem (Springer-Verlag, 2007)
The purpose of this study was to compare the biomechanical properties of four volar fixed-angle fracture fixation plate designs in a novel sawbones model as well as in cadavers. Four volar fixed angle plating systems (Hand Innovations DVR-A, Avanta SCS/V, Wright Medical Lo-Con VLS, and Synthes stainless volar locking) were tested on sawbones models using an osteotomy gap model to simulate a distal radius fracture. Based on a power analysis, six plates from each system were tested to failure in axial compression. To simulate loads with physiologic wrist motion, six plates of each type were then tested to failure following 10,000 cycles applying 100N of compression. To compare plate failure behavior, two plates of each type were implanted in cadaver wrists and similar testing applied. All plate constructs were loaded to failure. All failed with in apex volar angulation.The Hand Innovations DVR-A plate demonstrated significantly more strength in peak load to failure and failure after fatigue cycling (p value < 0.001 for single load and fatigue failure). However, there was no significant difference in stiffness among the four plates in synthetic bone. The cadaveric model demonstrated the same mode of failure as the sawbones. None of the volar plates demonstrated screw breakage or pullout, except the tine plate (Avanta SCS/V) with 1 mm of pullout in 2 of 12 plates. This study demonstrates the utility of sawbones in biomechanical testing and indicates that volar fixation of unstable distal radius fractures with a fixed angle device is a reliable means of stabilization.